Competitve Strategic Management Practices within the Telecommunications Industry Players in the Sultanate of Oman - Varghese, Shery (2011)
For running a successful organization in a highly competitive environment, strategic management practices remain an inevitable factor. Many researchers have been debating on the actual definition and significance of this subject and trying their best to apply the facts to application. Like giving high importance to the fields of sales, marketing and operations, companies today do neglect the idea of bringing in an exclusive department consisting of strategists.The Sultanate of Oman is no exception to understanding the actual value of strategic management. Oman as a country is very new to competitive environment unlike India where every other day a new organization emerges into the industry. It is only in the last five years that Oman has been feeling the need to understand strategic management with increasing competition since then. It is this awareness that has made the writer chooses the telecommunications sector (by far one of the most competitive industries after the Automobile distributors) in Oman.This project management hence discusses the operations of three companies within the telecommunications industry. According to the data retrieved from the internet, through interviews with the concerned officials of the companies and also critics and strategists review, the project has gone through the phase of analysis in understanding how different each of the telecommunication companies are from each other despite being in the same industry. Issues are thus discovered within the industry and those followed by each of the organizations. Thereafter surveys have been conducted to give an understanding on the consumer perception to each brand and their likeness. Finally appropriate suggestions have been made on each of the telecom sector on how to improve their strategic management practices and thereby strengthen their company portfolio and subsequently increase their market share.